Supply Chain Risk Mitigation for Logistics Service Companies - Achmad, Fandi; Sriwana, Iphov Kumala; Rumanti, Augustina Asih (TALENTA Publisher, 2023)
The increasing use of expedition services due to the Covid-19 pandemic has also increased various types of risks in companies. This study discusses solutions to the complexity of supply chain management in the expedition services industry due to pandemic Covid-19. This study aims to analyze the risk of security management systems based on every activity in the supply chain of an expedition company. The method used in this study is the matrix risk assessment to determine the risk ranking by multiplying the possibilities and consequence values. Descriptive analysis approaches and in-depth interviews are needed to identify the types of risks in the supply chain of PT.X. The application of risk assessment consists of five stages: development mapping of supply chains, risk identification, risk assessment, risk response development, and risk response control. The results of this study indicate that three types of extreme risks need to be handled in priorities by providing proposed mitigation, namely bad weather, road accidents, and damaged items. Risk mitigation strategies are carried out to prevent the types of extreme risks in the company.